Analysis of the Pedigree and Ancestors of the Cutting Population of the Quarter Horse Breed - Yahagi Rodrigues, Larissa [UNESP]; da Silva Faria, Ricardo António [UNESP]; de Vasconcelos Silva, Josineudson Augusto II. [UNESP] (Elsevier, 2021)
The aim of this study was to evaluate the genetic diversity and to identify the most influential ancestors in the population of Brazilian Quarter Horses participating in cutting competitions. Data from 1,590 elite horses born between 1970 and 2015, which participated in cutting competitions between 1981 and 2018, were evaluated based on the pedigree file that contained 5,832 animals born since 1834. Evaluation of the quality of the pedigree data showed a mean number of known equivalent generations of 5.4 ± 1.5 and a mean generation interval of 11.7 ± 8.8 years. The inbreeding coefficient (1.98 ± 7.13%), relatedness coefficient (2.18 ± 0.01%), and individual increase in inbreeding (0.43 ± 0.01%) were low. The effective population size (Ne) was 136 animals. The probability of gene origin indicated effective numbers of founders, ancestors, and founder genomes of 255, 37, and 23 animals, respectively. The number of founders and ancestors was 1,852 and 899 animals, respectively, with 10, 50, and 100 ancestors explaining 39.2%, 67.9%, and 91.6%, respectively, of the genetic diversity of the population. The five most influential ancestors were Doc Bar, Peppy San Badger, Freckles Playboy, Poco Lena, and High Brow Cat, accumulating 30.7% of the marginal genetic contributions of the population. Few ancestors were responsible for the genetic diversity, resulting in the narrowing of the initial genetic base. Breeders depend on a small group of ancestors, which could be corrected by increasing the number of breeding animals and by directed mating using ancestors of different origins.
Keywords: Ancestors; Founders; Genetic drift; Inbreeding